2022
DOI: 10.3390/ani12091200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Organic and Inorganic Sulfur on the Performance of Coccidiosis Vaccine Challenged Broiler Chickens

Abstract: The objective of this study was to evaluate the effects of dietary sulfur from either organic (methyl sulfonyl methane, MSM) or inorganic (sodium sulfate, SS) sources on the growth performance of broiler chickens challenged against a high-dose coccidiosis vaccine. A total of 320 day-old Ross 308 broiler chicks were randomly placed into 32 pens of 10 birds each (keeping 16 pens/control group and 8 pens/treatment group until 21 days post-hatch) and reared for 28 days. The experimental diets were formulated by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sulfur compounds can potentially kill Eimeria by destroying the sporozoites ( 21 ). Garlic in multiple forms, i.e., essential oils, extracts, and powders, has been used to treat coccidiosis, and it has shown anticoccidial activity due to these compounds ( 89 , 120 , 124 , 217 , 289 , 290 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur compounds can potentially kill Eimeria by destroying the sporozoites ( 21 ). Garlic in multiple forms, i.e., essential oils, extracts, and powders, has been used to treat coccidiosis, and it has shown anticoccidial activity due to these compounds ( 89 , 120 , 124 , 217 , 289 , 290 ).…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine failure is the primary issue observed with anticoccidial vaccines ( 30 , 85 , 88 ). Vaccine failure results in vaccine-induced coccidiosis ( 89 ). Moreover, anticoccidial vaccines provide only temporary protection and require frequent repetition, especially in breeders and layer birds ( 90 , 91 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E is an essential dietary antioxidant for maintaining birds' health and immune system (Jeon et al, 2022). Marsh et al (1981) demonstrated that the nutritional deficiency of vitamin E causes an impaired immune system which is measured by the humoral immune response to the sheep erythrocytes in broilers.…”
Section: Vitaminsmentioning
confidence: 99%